GPA, retention and persistence for developmental education students enrolled in learning strategies courses as mitigated by motivation and modality - Lassiter, Allison O'Leary (Kansas State University, 2023)
Developmental education is a subject of increasing interest, and many current educational reforms are aimed at helping developmental students to succeed. As such, outcomes for developmental students are important for evaluating programs and supports offered to students in this situation. One such support is learning strategies coursework. Prior research has supported the efficacy of these courses (Boylan et al., 1997; Goldrick-Rab, 2010; Kolenovic et al., 2013; Rutschow & Schneider, 2011), so at the institution of study, one such course was offered to developmental students for free as a means to help developmental students navigate the transition to credit-bearing courses. For this study, GPA, retention, and persistence were obtained in order to evaluate the impact of this course on students. For students who took the scholarship as opposed to students who did not, retention (reenrollment the subsequent semester) and persistence (reenrollment, transfer, or graduation) were higher for students who took the course as opposed to those who did not when matching on demographic characteristics and prior GPA. As motivational traits are correlated with GPA (Almalki, 2019; Fong et al., 2021), persistence and retention as well, the results from the LASSI, a study skills inventory that measures skill, will and self-regulation, were evaluated to determine if there was correlation. As a result of the course, outcomes in attitude, concentration, motivation, test strategies and time management were all increased from pre to post-test, and all scores except attitude, concentration and test strategies post-test scores were correlated with higher GPA. Concentration, motivation and test strategies post-test scores were correlated with higher persistence, and no scores correlated with retention alone. Finally, as some research indicates that developmental students are more at risk in online learning (Jaggers & Xu, 2010; Xu & Jaggers, 2013), it is important to evaluate if online coursework disadvantages our developmental students. Students who take the learning strategies course face to face do have better grades overall, but do not have a significantly higher GPA or persistence and retention rate. Overall, we can recommend that coursework for developmental students has the potential to increase retention and persistence, that effort should be expended on increasing those motivational characteristics and that we should continue to offer the coursework both online and in person with that caveat that grades may be higher in face-to-face coursework.
Keywords: Developmental education; Motivation; Persistence; GPA; Learning strategies; College success